The People’s popularity of the people towards the Bhumjai Thai Party Ban Klueng Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province - Saipin, Juthamas; Auraiwan, Duangporn (Journal of Public Administration Chiang Rai Rajabhat University, 2025)
The purposes of this research are to 1. Study the level of political popularity of the people towards the Bhumjaithai Party 2. Study the differences of personal factors affecting the political popularity of the people towards the Bhumjaithai Party Ban Klung Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province. This research was a quantitative research using a questionnaire as a research tool and analyzing the data using a statistical method using a ready-made computer program. The total population used in the research was 2,012 people, calculated from a sample of 334 people, derived from the formula of Taro Yamane at a reliability level of 95% and a sampling error of .05. The sample was collected using a questionnaire as a tool for data collection. The statistics used for data analysis were percentage, mean, and standard deviation, Independent T-test, and One-way ANOVA. The research results found that 1) The level of political popularity of the people towards the Bhumjaithai Party Ban Klung Subdistrict, Bang Sai District, Phra Nakhon Si Ayutthaya Province consisted of 3 aspects: political party, candidate for the House of Representatives, and potential to be a source of support for urban development for the people. The overall results were at a high level. The mean value was 4.05 and the standard deviation was .676. 2) Personal factors in terms of income were related to political popularity, while personal factors in terms of gender, age, education, status, and occupation had no significant effect.